Left temporal lobe structural and functional abnormality underlying auditory hallucinations - Hugdahl, Kenneth; Løberg, Else-Marie; Nygård, Merethe (Frontiers in Neuroscience, 2009)
In this article, we review recent findings from our laboratory that auditory hallucinations in schizophrenia are internally generated speech "mis-representations" lateralized to the left superior temporal gyrus and sulcus. Such experiences are, moreover, not cognitively suppressed due to enhanced attention to the "voices" and failure of fronto-parietal executive control functions. An overview of diagnostic questionnaires for scoring of symptoms is presented, together with a review of behavioural, structural and functional MRI data. Functional imaging data have either shown increased or decreased activation depending on whether patients have been presented an external stimulus or not during scanning. Structural imaging data have shown reduction of grey matter density and volume in the same areas in the temporal lobe. The behavioral and neuroimaging findings are moreover hypothesized to be related to glutamate hypofunction in schizophrenia. We propose a model for the understanding of auditory hallucinations that trace the origin of auditory hallucinations to uncontrolled neuronal firing in the speech areas in the left temporal lobe, which is not suppressed by volitional cognitive control processes, due to dysfunctional fronto-parietal executive cortical networks.